2007
DOI: 10.1021/ja073144n
|View full text |Cite
|
Sign up to set email alerts
|

Base-Promoted Tautomerization of Imidazole Ligands to N-Heterocyclic Carbenes and Subsequent Transmetalation Reaction

Abstract: Imidazole complexes of manganese(I) are transformed into their corresponding N-heterocyclic carbene derivatives by means of acid−base treatments; the subsequent sequential transmetalation reaction of the carbene to gold(I) proceeds through isolable heterometallic intermediate species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
87
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 15 publications
12
87
0
1
Order By: Relevance
“…[24] The Mo1ÀN1 distance of 2.219 (8) , is similar to other molybdenum(II) imidazole distances previously reported.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…[24] The Mo1ÀN1 distance of 2.219 (8) , is similar to other molybdenum(II) imidazole distances previously reported.…”
supporting
confidence: 83%
“…[6,7] In 2007 Ruiz and Perandones published the transformation of an imidazole Mn I compound into an NHÀNHC complex by a deprotonation/ protonation sequence (see Scheme 1a). [8] About at the same time, we found that the deprotonation reaction of the analogous rhenium compounds, [ReA C H T U N G T R E N N U N G (bipy)(CO) 3 A C H T U N G T R E N N U N G (N-RIm)]OTf (R = methyl, mesityl; OTf = triflate), led to a completely different kind of product. [9] As shown in Scheme 1b, the re-A C H T U N G T R E N N U N G action of the rhenium species with a strong base deprotonated the imidazole C2 À H group, and the so formed carbeniate attacked a C ortho of the adjacent 2,2'-bipyridine ligand.…”
Section: -C 4 H 7 )A C H T U N G T R E N N U N G (Bipy)(co) 2 a C H Tmentioning
confidence: 88%
See 1 more Smart Citation
“…Subsequent attempts to deprotonate the C 2 carbon atom led to an intermediate which upon protonation with NH 4 PF 6 reacted to give the complex with a C 2 metalated NH,NPh-stabilized carbene ligand. [358] This base-catalyzed tautomerization [359] of an imidazole complex into an NHC complex could be of general applicability for the preparation of NHC complexes. Similar complexes with NH,NR-stabilized benzimidazolin-2-ylidene ligands have been obtained from N-alkylbenzimidazole (Scheme 97).…”
Section: Discussionmentioning
confidence: 98%
“…For example, in some syntheses of NHC complexes, free NHCs are made by deprotonating imidazolium salts; this route is precluded in making PNHCs, because the most acidic proton on the imidazolium salt precursor would be that on one of the nitrogens. Some PNHC complexes are made by coordination of a 1-alkylimidazole to a metal fragment, followed by deprotonation with the appropriate base at C-2, migration of the metal fragment to C-2, followed by protonation with the appropriate acid [3][4][5]. A variant on this scheme starts with C-2 deprotonation, installation of the metal at C-2, and protonation [6][7][8].…”
Section: Introductionmentioning
confidence: 99%